A prospective study of clinical presentation, management, and post-operative complications of benign parotid swellings - G. S. R., Hareesh; Pulipati, Prabhakar Naidu (International Surgery Journal, 2019)
Background: The incidence of parotid tumours is between 1-3/100000 per year, most of them are benign and 80% benign tumours are pleomorphic adenoma. Their management is more troublesome because of their late presentation, poor economic condition and lack of awareness of health. Methods: This is a prospective observational study carried out from August 2016 to march 2018 in the Department of General Surgery, S.V.R.R.G.H., Tirupati. Detailed pre-operative workup done operative findings and post-operative complications were noted and biopsy reports analyzed. Results: Total 30 patients were included in the study of which 28 were pleomorphic adenoma and 2 were Warthin’s tumor. Post-operative complications and histopathology were studied and analyzed. Conclusions: Pleomorphic adenoma was most common benign tumor. Conservative superficial parotidectomy was the common surgical procedure done. Most common complication was temporary facial nerve palsy. No recurrence was seen in 6 months follow up.